2023
DOI: 10.3390/fermentation9050437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guanidinoacetic Acid on Ruminal Fermentation and Greenhouse Gas Production Using Fresh Forage and Silage from Different Maize (Zea mays L.) Genotypes

Abstract: Guanidinoacetic acid (GAA) is a feed additive that promotes growth in animals, while maize (Zea mays L.) is used for the mitigation of ruminal greenhouse gases. However, it is unknown if GAA affects the efficiency of maize in mitigating gases or if there is synergy between them. Therefore, the objective of this study was to evaluate the in vitro production of total gas, methane (CH4), carbon monoxide (CO), and hydrogen sulfide (H2S), ruminal fermentation characteristics, and the CH4 conversion efficiency of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…However, it has been reported that the addition of GAA in the diet can decrease the asymptotic production and the production rate of GP [44], which was observed in the AH100 diet when increasing the dose of GAA, which is attributed to the proportion of short-chain fatty acids (SCFA), since GAA favors the formation of propionate [45], an SCFA that produces less gas compared to acetate and butyrate [46]. In addition, the lag phase also increased in this diet; although it did not show a trend with an increasing dose of GAA, this increase can be attributed to the time that ruminal microorganisms require to adapt to the presence of GAA, since it is susceptible to degradability when it is not rumen protected [47], and microorganisms can use it as a source of energy and nitrogen to synthesize their proteins [45].…”
Section: In Vitro Ruminal Total Gas Productionmentioning
confidence: 98%
“…However, it has been reported that the addition of GAA in the diet can decrease the asymptotic production and the production rate of GP [44], which was observed in the AH100 diet when increasing the dose of GAA, which is attributed to the proportion of short-chain fatty acids (SCFA), since GAA favors the formation of propionate [45], an SCFA that produces less gas compared to acetate and butyrate [46]. In addition, the lag phase also increased in this diet; although it did not show a trend with an increasing dose of GAA, this increase can be attributed to the time that ruminal microorganisms require to adapt to the presence of GAA, since it is susceptible to degradability when it is not rumen protected [47], and microorganisms can use it as a source of energy and nitrogen to synthesize their proteins [45].…”
Section: In Vitro Ruminal Total Gas Productionmentioning
confidence: 98%